The Influence of YouTube Beauty Vloggers on Cosmetic Consumer Decisions with Product Quality as a Moderating Variable - Ernawati; Septa Intiar; Iswanto; Aresyama Hein Temmar; Ana Yuliana (Yayasan Inovasi Kemajuan Intelektual, 2025)
The research is a quantitative study with an explanatory approach, which makes previous research the main reference for creating, modifying, and proving the hypotheses in this study/. The data used in this study are primary data researchers obtained from consumers who purchased cosmetic products recommended by vloggers on the YouTube platform. The data used in this study were analyzed using the smart PLS 4.0 analysis tool. The result in this article shows that the YouTube Beauty Vloggers variable can have a positive relationship direction and a significant influence on Cosmetic Consumer Decisions because the P-Values ​​are positive and below the 0.05 significance level, namely 0.008. These results are in line with the fifteenth study. The difference is that this study's independent and dependent variables are more specific, namely, YouTube Beauty Vloggers and Cosmetic Consumer Decisions. These results also show that YouTube Beauty Vloggers can improve Purchasing Decisions, increase market share, and improve the company's financial stability. In addition, the product quality variable can also moderate the influence of the YouTube Beauty Vloggers variable on the cosmetic consumer decisions variable because the P-values ​​are also positive and below the 0.05 significance level, namely 0.000, which is more significant than direct testing. Thus, it can be concluded that this article's first and second hypotheses can be accepted and proven.